The relationship between payday and violence in Guatemala. (7th October 2012) - Ramirez, D; Branas, CC; Wu, E
Abstract : Background: In 1996, Guatemala emerged from a decades-long civil war, yet currently faces the highest rates of violence since then. From 1999 to 2006, homicides increased 120% in a country now considered one of the most violent places on earth, outside of active war zones. Reports suggest violence rises during the middle and last days of every month, when wages are paid, but no study supports this payday-violence connection. Aim: To determine if fatal violence is associated with payday, adjusting for gender, age and time. Methods: Secondary data analysis of autopsies registered to the Guatemalan National Institute of Forensic Sciences in 2008, estimated mean numbers of deaths during paydays versus non-paydays. Regression analyses were undertaken to account for the effects of gender, age, and time. Results: A total of 11 896 autopsies of people≥10-years-old were analysed. Of these, 84.5% were male, with a mean age of 35.7 years. 39.6% of deaths were caused by gunfire, 2.9% by stabbing, and 57.5% by other mechanisms. Regression modelling showed the risk of homicides during paydays was lower compared to non-paydays, though this was not significant (p=0.145). The mean number of deaths did significantly differ by day-of-week (p<0.0001) and month (p<0.001), with highest means from Saturday-Monday and October-December. Significance: These results help to understand the role of payday and other covariates as potentially modifiable risk factors for violence. Future research and interventions might consider specific time markers, such as days and months, for the prevention of violence in Guatemala and similarly situated countries.